Understanding chipped stone tools - Hayden, Brian (Principles of archaeology, 2022)
"This is a unique and engaging book on prehistoric stone tools. It advocates an experiential approach in which analysts try to understand stone tool designs from the users' perspectives, and employs a universal logic of designing tools to solve practical problems and evaluating various possible solutions. However, to do so it is also necessary to understand how stone can be mechanically modified to serve specific functions. The author enlists a rich array of ethnographic observations and considerable background as a flintknapper to show the basic ways in which stones can be flaked and modified and what these characteristics can reveal about prehistoric problem-solving strategies and design constraints. This is an invaluable primer for anyone contemplating the study of prehistoric stone tools."--